Ensino de música por meio de teclados de percussão: uma experiência com o Grupo Marimbas de Maracanaú – Ceará - Correia, José Rogério dos Santos (2015)
This paper deals with the music education from an experience with children and adolescents in the city of Maracanaú - Ceará, which resulted in the formation of an instrumental percussion group called “Marimbas” Group. It was studied the process of teaching and learning from educational practices developed in the group in order to improve their musical performance and contribute to the formative aspects in the music education field. In compliance with the goals the results of the methods used were analyzed, there was a historic of musical training experience in “Marimbas” Group and organized a didactic material containing guidelines and instrumental technique exercises for percussion keyboards. I used as theoretical support the pedagogical proposal of the German music educator Carl Orff and methods of technical studies for percussion keyboards of Ney Rosauro and Morris Goldenberg. Besides these, also it served as a support the works of Cruvinel (2005), Suplício (2011) among others. The methodology used was a qualitative research outlined through a case observation, with the contribution of the authors Bogdan and Biklen (1994), Yin (2001) and Gil (2009). As instruments for data collection were used: literature, documents and natural participant observation. The results demonstrate the relevance of pedagogical practices developed in “Marimbas” Percussion Group of Maracanaú and enable these practices related to music education to be shared with other educators.